Pain education program using games and online teaching: beyond the COVID-19 pandemic - Mimi Mun Yee Tse; Tyrone Tai On Kwok; Timothy Chung Ming Wu; Kin Pong To; Percy Poo-See Tse; Jiafan He (Critical Public Health)
Chronic pain affects older adults’ quality of life, worsened by COVID-19 healthcare disruptions. This study introduces the Gamified Web-based Pain Management Program (GAP), a digital tool using gamification to improve pain education. Developed with the Model of Technology Adoption by Older Adults, GAP was tested in a quasi-experimental pilot study. Four community-dwelling adults (aged ≥65) participated for 4 weeks. Pain was assessed using the Brief Pain Inventory (BPI). Post-intervention, pain severity dropped from 3.44 to 1.31 and interference from 2.39 to 0.43, with positive usability feedback. Limits include the small sample and no control group. Larger, controlled trials are needed to confirm efficacy. GAP shows promise for pain management in older adults during healthcare challenges.